VICARIOUS SELECTION EXPLAINS SOME PARADOXES IN DIOECIOUS FIG POLLINATOR SYSTEMS - Grafen, A; Godfray, H (1991)
Fig trees (Ficus spp.) are pollinated by small hymenopteran wasps that develop within the fig. In dioecious species, female wasps enter and pollinate 'female' figs that produce only seeds and within which the wasp is unable to reproduce. A resolution for three paradoxes in the biology of dioecious fig-pollinator systems is suggested: (i) why wasps enter female flowers, (ii) why they maintain structures and behaviours needed to pollinate female figs, despite the absence of any direct selection on these phenotypes and (iii) why wasps entering male flowers go through the behaviours that would be required to pollinate female figs. Whereas it is obviously in a female fig's interest to conceal her sex from the wasps, it is argued that it is also in a male fig's interest to do so, because the male will benefit only from raising female wasps that, when they leave, successfully find, enter, and pollinate female figs (even though this will be fatal to the wasps).